Identification of Marine Waste by Type and Mass in Lae-Lae Island Makassar City: Identifikasi Sampah Laut Berdasarkan Jenis dan Massa di Perairan Pulau Lae-Lae Kota Makassar - Angkasa Putra; Nining Wahyu Ningsih; Muh. Rafly Anggara; Herianto Suriadin (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2020)
Garbage in coastal areas is one of the complex problems faced by an area that is close to the coast or the coast which has several rivers that empty into the sea. Marine debris, especially inorganic (undergradable) waste, is the main enemy, whose numbers do not decrease over time and its existence tends to be neglected. The impact caused by this type of waste can threaten the survival and sustainability of biota in the waters. The purpose of this study was to determine the amount, type, mass, and density of inorganic marine debris in the waters of Lae-Lae Island, Makassar City. This research was conducted in May-June 2019 on Lae-Lae Island. The garbage collection method is carried out at 3 stations, where Station 1 is in the North, Station 2 is in the West and Station 3 is in the South of Lae-Lae Island. In a transect that is stretched along the coastline and then divided into 3 plots at each station with a size of 50 m x 20 m. Then, collect every type of trash found on the plot. The results showed that the straw type soft plastic waste was mostly found in each research station. The total mass of waste obtained on Lae-Lae Island is 65.64 kg/0.003 km2 and the average density of waste on Lae-Lae Island according to the number of pieces is 1.82 items/m2 and for the average density by weight is 21, 87 g/m2.